1992
DOI: 10.1111/j.1751-1097.1992.tb08511.x
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐induced Electron Transfer From Nucleotides to Ruthenium‐tris‐1,4,5,8tetraazaphenanthrene: Model for Photosensitized Dna Oxidation

Abstract: Abstract— The luminescence quenching of ruthenium‐tris‐l,4,5,8‐tetraazaphenanthrene [Ru(tap)32+] by nucleotides approaches the diffusion rate only with guanosine‐5′‐monophosphate (GMP), the most reducing nucleotide, and leads to an electron transfer with the production of the monoreduced complex and the oxidized base. The resulting deprotonated GMP(‐H)radical recombines with the monoreduced complex according to a bimolecular equimolar process. The pH dependence of the decay of the transient reduced complex, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 31 publications
6
81
0
Order By: Relevance
“…8) is lower than that in air also suggests that besides the reactive oxygen species, a direct oxidative process may contribute to the cleavage. Photoinduced electron transfer from the guanine to the excited complex has been demonstrated as the primary process that initiates DNA cleavage, and guanine is the easiest nucleobase to oxidize [54]. Briefly, making the complex more oxidizing in the excited state will accelerate the electron transfer process, thus promoting the DNA cleavage.…”
Section: Luminescence Spectroscopic Studiesmentioning
confidence: 98%
“…8) is lower than that in air also suggests that besides the reactive oxygen species, a direct oxidative process may contribute to the cleavage. Photoinduced electron transfer from the guanine to the excited complex has been demonstrated as the primary process that initiates DNA cleavage, and guanine is the easiest nucleobase to oxidize [54]. Briefly, making the complex more oxidizing in the excited state will accelerate the electron transfer process, thus promoting the DNA cleavage.…”
Section: Luminescence Spectroscopic Studiesmentioning
confidence: 98%
“…It is well known that the coiled circular plasmid is transformed, just by one single nick, into its open circular form. It has been demonstrated that these photocleavages by the Ru-TAP complexes originate also from the PET process from a G base [23]. On the basis of these results, we should thus complete the photochemical reactions scheme shown in figure 1 by the addition of a supplementary reaction, subsequent to the PET process, i.e.…”
Section: Applications For Bi-adduct Formation With Two Absorbed Photomentioning
confidence: 99%
“…As explained above, the conditions to produce a mono-adduct of a G base of a mono-or polynucleotide to a Ru-TAP complex such as that shown in figure 2 have been fully investigated previously [23,24]. The formation of bi-adducts was first discovered with another complex, [Ru(HAT) 2 phen] 2+ (HAT = 1,4,5,8,9,12-hexaazatriphenylene) (figure 3a) [32].…”
Section: Applications For Bi-adduct Formation With Two Absorbed Photomentioning
confidence: 99%
“…8) is lower than that in air also suggests that, besides the reactive oxygen species, a direct oxidative process may contribute to the cleavage. Photoinduced electron transfer from the guanine to the excited complex has been demonstrated as the primary process, which initiates DNA cleavages [45]. Briefly, making the complex more oxidizing in the excited state will accelerate the electron-transfer process, thus will promote the DNA cleavages.…”
mentioning
confidence: 99%